S2_2 Astronomical Tidal Energy - Erojo, Anthony; Berry, Tom; Taylor, Ben (Physics Special Topics, 2017)
If the Earth ever found itself in the unlikely situation of suddenly orbiting an intermediate black hole of mass 1*103 mass of the sun [1], a large problem we would face would be the lack of heat that we originally received from the sun through solar energy. An avenue of hope for our problem would be to see if the tidal energy produced by the black hole would be enough to match the energy that we would receive from the sun, which is 1.74*1017W [2]. We decided to use an intermediate black hole as an example but the concepts and maths used in this paper should be applicable to any black hole. The output of the tidal energy was calculated to be 1.47*107W which is a factor of over a billion times smaller than what we receive from the sun. This would mean that the Earth would be unable to maintain its current surface temperature resulting in life being exposed to a colder and more hostile environment.